2021
DOI: 10.5500/wjt.v11.i6.220
|View full text |Cite
|
Sign up to set email alerts
|

Post-transplant erythrocytosis after kidney transplantation: A review

Abstract: Post-transplant erythrocytosis (PTE) is defined as persistently elevated hemoglobin > 17 g/dL or hematocrit levels > 51% following kidney transplantation, independent of duration. It is a relatively common complication within 8 months to 24 months post-transplantation, occurring in 8%-15% of kidney transplant recipients. Established PTE risk factors include male gender, normal hemoglobin/hematocrit pre-transplant (suggestive of robust native kidney erythropoietin production), renal artery stenosis, patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 63 publications
1
21
1
Order By: Relevance
“…Results were comparable to the previous studies. [16,17] In our study, frequency of PTE was found in 23 (19.5%) cases and 95 (80.5%) cases were without PTE. Approximately 30% of individuals were found to have PTE in previous trials.…”
Section: Discussionsupporting
confidence: 46%
“…Results were comparable to the previous studies. [16,17] In our study, frequency of PTE was found in 23 (19.5%) cases and 95 (80.5%) cases were without PTE. Approximately 30% of individuals were found to have PTE in previous trials.…”
Section: Discussionsupporting
confidence: 46%
“…4 The median time to development of PTE in our study was 360 days, which is also in accordance with previous reports 5 There are a few predisposing risk factors that are thought to contribute to the development of PTE. Male gender is a well-established one, 15,31,33 with most studies showing much higher frequency of men among PTE patients. In our study, 90% of PTE patients were men, compared with only 64% male prevalence in the whole kidney transplanted population.…”
Section: Discussionmentioning
confidence: 99%
“…146,147 It usually develops within the first 2 years, with spontaneous resolution reported in one fourth of patients within 2 years of diagnosis. 146 Predisposing factors include male gender, preserved glomerular filtration rate, rejection-free course, retained native kidneys, long pretransplant dialysis course, absence of anemia pretransplant, renal artery stenosis, polycystic kidney disease, and glomerulonephritis. 146 In earlier studies, it was associated with increased risk of thromboembolic events, which has not been the case in a contemporary series.…”
Section: Erythrocytosis Associated With Renal Transplantmentioning
confidence: 99%
“…146 Predisposing factors include male gender, preserved glomerular filtration rate, rejection-free course, retained native kidneys, long pretransplant dialysis course, absence of anemia pretransplant, renal artery stenosis, polycystic kidney disease, and glomerulonephritis. 146 In earlier studies, it was associated with increased risk of thromboembolic events, which has not been the case in a contemporary series. 148 The mechanism remains obscure but is felt to be multifactorial with excessive Epo production driven by renin-angiotensin, IGF-1, and endogenous androgens.…”
Section: Erythrocytosis Associated With Renal Transplantmentioning
confidence: 99%